Term Mediation in Modern Scientific Research on Translation - A. S. Kinderknekht; V. V. Kolada (Научный диалог, 2022)
The article is devoted to the definitional analysis of the term mediation in the scientific communication of translation researchers and the rational grounds for introducing a new word into the terminological system of the translation science branch of scientific knowledge. Research methods: information search of modern foreign and domestic scientific studies on the keywords mediation and mediatsiya, definitional and contextual analysis of the specified pair of terms in scientific research on translation in Russian, English and French. The authors raise the issue of a certain confusion in the use of the term to refer to various kinds of intermediary activity. It turns out that in the field of translation, mediation is most often understood as a process of acting as an intermediary and is a type of social interaction between different interlocutors with the help of an interpreter. As a result of the study, it is found that the introduction of the term mediation into scientific communication is determined by the need to designate a special kind of cultural mediation, in which the translator plays a more active role, bringing him closer to the mediator as a intermediary in controversial and conflict situations. The relevance of the use of the term here is connected with the problems of intercultural and sociocultural mediation in migration processes.